A cross-sectional study on the level of knowledge and attitude on diabetes mellitus among the population of 20 years and above in Kampung Susur Jambu Indah, Sarikei from 15th February to 11th April 2008 - Nor Azura, binti Abu; Yam, Wai Cheong; Ong, Wee Leen; Isnani, binti Sutiman; Fann, Rui Jeat; Poon, Tuck Choy; Liau, Felix Yee Fan; Erenna Khairan, binti Md Saleh; Mohd Aminuddin, bin Ab. Ghani; Amila Sariati, Mahd Shukry; Roshafiza, Jaffar @ Harun; Goh, Soo Ning; et al. (Universiti Malaysia Sarawak, (UNIMAS), 2008)
Knowledge and attitude of diabetes mellitus are important because it plays a major role in the prevention of this disease. Thus it is crucial to study these aspects in order to know the gaps among the sampled population. The objective of this research is to study the level of knowledge and attitude regarding diabetes among the sampled population aged 20 years and above of Taman Susur Jambu Indah, Sarikei from 15th February until 11th April 2008. A cross-sectional study was done on a sampled population of 268 respondents chosen by universal sampling. Data collection was conducted by using an questionnaire guided interview. Data entry and analyses were done using SPSS version 13.0, with parametric tests including ANOVA, chi-square test, independent `t' test, Fisher exact test and Pearson's correlation test, and non-parametric tests including Mann-Whitney test and Kruskal-Wallis test. Based on the results, the total score of knowledge was 94.78% with a mean score of 23.95. There was significant correlation between level of knowledge and level of education, household income and family history of diabetes (p<0.05). On the other hand, there was no significant relationship between level of knowledge with age and gender (p>0.05). Overall percentage of positive attitudes among the respondents was very high, 99.25%. There was positive correlation between level of attitude with the level of education (p<0.05). Conversely, there were negative relationship between level of attitude with age, gender, family history of diabetes and household income (p>0.05). In conclusion, influence on knowledge axle attitude is multifactorial. The better level of knowledge will reflect the better level of attitude. However, the attitude level is almost perfect in the sampled population compare to level of knowledge which showed that there was no attitudinal problem. So the intervention programme will mainly focus on increasing the level of knowledge of respondent toward diabetes.